2015
DOI: 10.1021/om501330h
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Direct Ortho Aroylation of 2-Phenoxypyridines with Aldehydes and Catalytic Mechanism Investigation

Abstract: A direct ortho aroylation of 2-phenoxypyridines with aldehydes leading to aryl ketones by the use of palladium(II) acetate, tert-butyl hydroperoxide, and chlorobenzene as the catalyst, oxidant, and solvent, respectively, is presented. Intra-and intermolecular kinetic isotope effects, radical trapping, and controlled experiments were carried out to support the proposed catalytic mechanism for the reaction. Syntheses of (2-hydroxyphenyl)-(phenyl)methanones and 1-hydroxy-9H-fluoren-9-ones directed from ortho-aroy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…22 In this report, detailed mechanistic experiments were conducted including intra- and intermolecular kinetic isotope effects, radical trapping, and controlled experiments. The authors proposed a Pd(III) or Pd(IV) π -complex as a key intermediate along the catalytic cycle and a reaction pathway that proceeds via conversion of the aldehyde to an acyl radical.…”
Section: Aldehydesmentioning
confidence: 99%
“…22 In this report, detailed mechanistic experiments were conducted including intra- and intermolecular kinetic isotope effects, radical trapping, and controlled experiments. The authors proposed a Pd(III) or Pd(IV) π -complex as a key intermediate along the catalytic cycle and a reaction pathway that proceeds via conversion of the aldehyde to an acyl radical.…”
Section: Aldehydesmentioning
confidence: 99%
“…More recently, Wu and co‐workers reported their study on the ortho ‐aroylation of 2‐phenoxypyridines with aldehydes 19. By using palladium(II) acetate, tert ‐butyl hydroperoxide, and chlorobenzene as the catalytic system, aryl ketones were formed generally in good yields (Scheme ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu and co-workers reported that the ortho-aroylation of 2phenoxypyridines with aldehydes could proceed efficientlyi n the presenceo ftert-butyl hydroperoxide (TBHP;S cheme 9). [13] The reactions produced mixture of mono-aroylateda nd di-aroylated phenol derivatives. However, these two products could be easily separated.…”
Section: Acylationmentioning
confidence: 99%